Dynamic simulation of carbon stocks in tropical lowland savanna in East Nusa Tenggara, Indonesia - Ahmad Almulqu, Aah; Boonyanuphap, Jaruntorn (Asian Health, Science and Technology Reports, 2017)
Tropical forest can stabilize CO2 concentration in atmosphere by absorbing CO2 through photosynthesis process and store it in forest biomass. Carbon stock information in forest biomass is required to facilitate carbon sink programme. This study aims to calculate carbon pools and carbon sequestration, and to simulate the dynamics of carbon stocks in the tropical lowland savanna by using the Carbon Accounting Simulation Software (CASS) programme. The study was located at Taman Wisata Alam Camplong (Camplong Nature Recreation Park), Camplong village, Kupang Regency, East Nusa Tenggara Province, Indonesia. Plots size of 20 m x 100 m were established in six study sites. The scenario for this research was divided into 3 scenarios i.e. Scenario 1 (Natural and traditional forest management) was applied for virgin dry forest and traditional agroforestry sites, Scenario 2 (Timber-based plantation forest management), and Scenario 3 (Non timber-based plantation forest management). The results show that the carbon concentration of Traditional agroforestry system (or Mamar forest) were up to 52% higher than virgin dry forest. Carbon stock of living vegetation and soil were increased with a decreasing of harvesting rotation and reached the highest level in Mamar forest (273.558 gC/m2/year and 344.042 gC/m2/year). Timber-based plantations with mixed species had the next higher value of carbon stock, and the non-timber-based plantation forest was the third. In the study sites, managing the dry forest for timber is compatible with maximizing carbon storage if appropriate harvesting practices are used.